Agro-food Business Strategies for Origin Labelled Products - Luis Miguel Albisu; Kate Corcoran (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
Traditional and typical food products are, at present, fully recognised by European Union institutions and regulations. The name Origin Labelled Products (OLPs) brings together all those food products, which have legal recognition under the EU legislation, defined as produced in a particular place or region, while complying with certain EU rules. The term includes products of either Protected Designation of Origin (PDO) or Protected Geographical Indication (PGI). Globalisation of food markets has reinforced the attractiveness of these products, as seen in the trend for consumers to appreciate locally produced products more in response to global brands and homogeneous food products. Food safety concerns among consumers, either rationally or emotionally driven, have contributed to the desire for established and traditional processes and origins in products. In this paper, the most important features that identify OLP enterprises and their business environment are described. Although they are small and medium size enterprises (SMEs), they have some distinctive features that might allow them to become more competitive. Following this, the principal characteristics of OLPs and their marketing characteristics are exposed. Future business strategies are discussed in the global economic context and a number of recommendations provided.
Keywords: 330; Lebensmittel; Herkunftsbezeichnung; Marketingmanagement; KMU; Lebensmittelmarkt; EU-Staaten